인지 라디오 네트워크에서 에너지 하베스팅을 고려한 에너지 효율적 자원 할당 방안 - 이기송(Kisong Lee); 이웅섭(Woongsup Lee) (한국정보통신학회논문지, 2016)
Recently, the energy harvesting technology in which energy is collected from the wireless signal which is transmitted by mobile communication devices, has been considered as a novel way to improve the life time of wireless sensors by mitigating the lack of power supply problem. In this paper, we consider the optimal sensing time and power allocation problem for cognitive radio systems, where the energy efficiency of secondary user is maximized while the constraint are satisfied, using the optimization technique. Based on the derived optimal solutions, we also have proposed an iterative resource allocation algorithm in which the optimal power and sensing time allocation can be found without excessive computations. The simulation results confirm that the proposed scheme achieves the optimal performance and it outperforms the conventional resource allocation schemes in terms of energy efficiency while the constraints are guaranteed to be satisfied. 무선신호로부터 전력을 수집하는 에너지 하베스팅 기술은 센서의 전원 부족 문제를 해결하고, 무선네트워크의 수명을 향상시킬 수 있는 방안으로 최근 큰 관심을 받고 있다. 본 논문에서는 최적화 기법을 이용하여 에너지 하베스팅이 가능한 인지 라디오 네트워크에서 제 2 사용자의 에너지 효율성을 최대화하기 위한 센싱 시간 및 파워 할당 해를 도출하고, 이를 이용하여 반복 기반의 자원 할당 알고리즘을 제안한다. 시뮬레이션을 통해 제안 방안이 최적의 에너지 효율을 달성함을 보이고, 기존방안(Max rate scheme)과의 비교를 통해 제안 방안의 우수성을 보인다.